The crystallization of MgO–Al2O3–SiO2–ZrO2 glass-ceramics with and without the addition of Y2O3 – a combined STEM/XANES study. Issue 67 (30th June 2016) - Seidel, Sabrina; Patzig, Christian; Höche, Thomas; Krause, Michael; Ebert, Martin; Hu, Yongfeng; Zuin, Lucia; Gawronski, Antje; Rüssel, Christian
Abstract : The crystallization of magnesium–aluminosilicate glasses is monitored, described and discussed via X-ray absorption spectroscopy and analytical transmission electron microscopy. Abstract : Glasses with the mol% composition of 51.9SiO2 /21.2Al2 O3 /21.2MgO/5.7ZrO2 without and with the addition of 2.5 mol% Y2 O3 were melted and subsequently transformed into glass-ceramics via annealing. Both glass-ceramics show strong differences in the microstructure and in the phase composition after crystallization at 950 °C for 5 h and subsequently at 1060 °C for different annealing times. In the glass without Y2 O3, the main crystal phase is a quartz solid solution accompanied by the precipitation of ZrO2 and spinel. By contrast, glass-ceramics without the presence of a quartz solid solution were observed after the crystallization of the Y2 O3 -containing glass, using the same heat treatment. This is confirmed by analytical scanning transmission electron microscopy analysis and X-ray absorption near-edge structure spectroscopy data gathered at the Zr L2 -, Y L2, 3 -, Si K- and Al L-edges. Furthermore, using X-ray absorption spectroscopy the coordination of the respective elements is analysed, and changes of the coordination during crystallization are monitored.